Pattern of Eye Health Care Services in a Tertiary Specialized Eye Hospital in Bangladesh - Zenith, Progga Sarker; Kadir, Syeed Mehbub Ul; Islam, Shirajul; Bhuiyan, Mahbubur Rahman; Faridi, Jamshed; Ferdausi, Nahid (Community Based Medical Journal, 2024)
A retrospective study was conducted in Sheikh Fazilatunnesa Mujib Eye Hospital and Training Institute, Gopalganj, Bangladesh, to analyze the trends of eye diseases in Bangladesh and surgical treatments provided by a tertiary eye hospital to manage them. A total of eighty-eight thousand nine hundred fifty-eight subjects attended the hospital for their ophthalmic checkup from the southern part of Bangladesh. Patience was evaluated according to their complaints; patient demographic data and medical history were retrospectively collected. Complete ophthalmic examination was performed. The study included 44,187 males and 44,771 females. Most of the patients were above 50 years while the toddlers were the least. The highest performed minor procedure was sac patency test and incision and curettage for chalazion was the minimum. regarding the major surgeries, cataract surgeries take the lead followed by DCR, DCT and intravitreal retinal injections. Cataract surgery and retinal injections were performed more in males whereas larger number of female patients underwent DCR and DCT. Most of the patients took their service from outpatient department. In a developing country like Bangladesh, mostly occurring ocular conditions like cataract and lacrimal apparatus diseases should be of utmost importance and National resources should be aimed at the management of such diseases. At the same time, care has to be taken to identify pediatric eye conditions at earlier age by raising awareness among parents. CBMJ 2024 July: vol. 13 no. 02 P: 235-242